Small molecule nicotinamide N-methyltransferase inhibitor activates senescent muscle stem cells and improves regenerative capacity of aged skeletal muscle - Neelakantan, Harshini (Biochem Pharmacol, 2019)
Aging is accompanied by progressive declines in skeletal muscle mass and strength and impaired regenerative capacity, predisposing older adults to debilitating age-related muscle deteriorations and severe morbidity. Muscle stem cells (muSCs) that proliferate, differentiate to fusion-competent myoblasts, and facilitate muscle regeneration are increasingly dysfunctional upon aging, impairing muscle recovery after injury. While regulators of muSC activity can offer novel therapeutics to improve recovery and reduce morbidity among aged adults, there are no known muSC regenerative small molecule therapeutics. We recently developed small molecule inhibitors of nicotinamide N-methyltransferase (NNMT), an enzyme overexpressed with aging in skeletal muscles and linked to impairment of the NAD(+) salvage pathway, dysregulated sirtuin 1 activity, and increased muSC senescence. We hypothesized that NNMT inhibitor (NNMTi) treatment will rescue age-related deficits in muSC activity to promote superior regeneration post-injury in aging muscle. 24-month old mice were treated with saline (control), and low and high dose NNMTi (5 and 10 mg/kg) for 1-week post-injury, or control and high dose NNMTi for 3-weeks post-injury. All mice underwent an acute muscle injury (barium chloride injection) locally to the tibialis anterior (TA) muscle, and received 5-ethynyl-2’-deoxyuridine systemically to analyze muSC activity. In vivo contractile function measurements were conducted on the injured TA muscle and tissues collected for ex-vivo analyses, including myofiber cross-sectional area (CSA) measurements to assess muscle recovery. Results revealed that muscle stem cell proliferation and subsequent fusion were elevated in NNMTi-treated mice, supporting nearly 2-fold greater CSA and shifts in fiber size distribution to greater proportions of larger sized myofibers and fewer smaller sized fibers in NNMTi-treated mice compared to controls. Prolonged NNMTi treatment post-injury further augmented myofiber regeneration evinced by increasingly larger fiber CSA. Importantly, improved muSC activity translated not only to larger myofibers after injury but also to greater contractile function, with the peak torque of the TA increased by ~70% in NNMTi-treated mice compared to controls. Similar results were recapitulated in vitro with C2C12 myoblasts, where NNMTi treatment promoted and enhanced myoblast differentiation with supporting changes in the cellular NAD(+)/NADH redox states. Taken together, these results provide the first clear evidence that NNMT inhibitors constitute a viable pharmacological approach to enhance aged muscle regeneration by rescuing muSC function, supporting the development of NNMTi as novel mechanism-of-action therapeutic to improve skeletal muscle regenerative capacity and functional recovery after musculoskeletal injury in older adults.